Analysis of proarrhythmic potential of an atypical antipsychotic drug paliperidone in the halothane-anesthetized dogs - Koki Chiba; Takeshi Wada; Yuji Nakamura; Xin Cao; Mihoko Hagiwara-Nagasawa; Hiroko Izumi-Nakaseko; Kentaro Ando; Koichiro Tanaka; Atsuhiko T. Naito; Atsushi Sugiyama (Elsevier, 2017)
Fatal cases with the use of atypical antipsychotic drug paliperidone have been reported; however, there was no clinical report describing paliperidone-induced torsade de pointes. In this study we assessed its electropharmacological effects together with its proarrhythmic potential in intravenous doses of 0.03, 0.3 and 3 mg/kg using the halothane-anesthetized dogs (n = 5), which could provide approximately 2, 20 and 200 times higher peak plasma drug concentrations than its therapeutic level, respectively. Paliperidone exerted potent vasodilator effect resulting in hypotension, which may be largely explained by its α1-adrenoceptor blocking action. In vivo electrophysiological results suggest that paliperidone may inhibit human ether-à-go-go-related gene K+ channel in a dose-related manner and modestly suppress Na+ channel in the in situ heart. The high dose of paliperidone may have some potential to induce early afterdepolarization that can trigger lethal ventricular arrhythmias, whereas the low and middle doses lack such proarrhythmic possibility, indicating that at least 20 times higher plasma concentration may be considered to be safe.